The Effect of "Learn English" Podcast on Students' Listening Skill of Biography Text at Eleventh Grade of SMKS YPSEI Palangka Raya - Fahri Husaini; Yulitriana Yulitriana; Elanneri Karani; Maida Norahmi (General English Education, 2024)
This research was conducted to find out the effect of “Learn English” podcast on students’ listening skill of biography text at the eleventh grade of SMKS YPSEI Palangka Raya. “Learn English” podcast is an application provided by the British Council and this application has so many advantages. This research used a pre-experimental design with one-group pre-test and post-test design. The researcher chose XI OTKP and XI TB class of SMKS YPSEI Palangka Raya as the research sample utilizing purposive sampling. The researcher applied multiple choice and short answer test as the instrument for data collection. The obtained data were then analyzed using the Paired Sample T-Test in SPSS version 22 at a significance level of 5% (0.05).  The result showed that the Sig. (2 tailed) = 0,001 < 0,05. As a result of Ha was accepted. To summarize, podcasts are an effective medium for teaching listening to students in the eleventh grade at SMKS YPSEI Palangka Raya. However, when implementing the media, a teacher must consider the students' listening habits. By taking into account the students' level of listening habit, a teacher can properly select the medium used to teach listening in order to increase the students' listening talent.